Answer:
-4 is the average rate of change from 3 to 4
Step-by-step explanation:
Average rate of change is defined as the fraction of change in f(x) value to change in x value.
Here we have x values as 3 and 4.
To find the average rate of change from x=3 to x=4
Average rate of change = change in f(x)/change in x
f(4) = -5^{4-3} +2 = -3\\f(3) = 1\\f(4)-f(3) = -3-1 =-4
Change in x = 4-3 =1
Answer:
x=3
Step-by-step explanation:
x^2 = 6x - 9
Subtract 6x from each side
x^2 -6x = -9
Add 9 to each side
x^2 -6x+9 = 0
Factor
what 2 numbers multiply to 9 and add to -6
-3*-3 = 9
-3+-3 =-6
(x-3)(x-3) = 0
Using the zero product property
x-3 =0 x-3=0
x=3 with multiplicity 2
So r is a number that when you add to t it will increase so its
T + r
You do mass divided by density